The angiotensin I converting enzyme gene and predisposition to high blood pressure - Harrap, S B; Davidson, H R; Connor, J M; Soubrier, F; Corvol, P; Fraser, R; Foy, C J; Watt, G C (Hypertension (Dallas, Tex. 1979), 1993)
Phenotypic abnormalities of the renin-angiotensin system have been associated with the predisposition to high blood pressure. The angiotensin I converting enzyme (ACE) gene has been implicated as a candidate gene. We examined the distribution of common alleles of the ACE gene and measured circulating components of the renin-angiotensin system and urinary sodium excretion in 170 young Caucasian adults with contrasting genetic predisposition to high blood pressure. Predisposition was defined on the basis of personal and parental blood pressure levels by using the four corners sampling method. Young adults with greatest predisposition who had high blood pressure and two parents with high blood pressure did not show any significant difference in the distribution of the markers of the ACE gene, either as genotype or allele frequencies, when compared with young adults with least predisposition who had low blood pressure and two parents with low blood pressure. Offspring with urinary sodium excretion above the median (143.4 mmol per day) also showed no significant differences in the distribution of ACE alleles or genotype between groups. Different genotypes were associated with different average serum ACE concentrations (p < 0.0001), but plasma angiotensin II and aldosterone showed no significant variation with ACE genotype. These results suggest that in a group of Caucasians selected from the general population, the ACE gene is not associated with genetic predisposition to high blood pressure. In this population common ACE gene allelic markers would not be useful indexes of susceptibility to hypertension.